2019
DOI: 10.1097/ncc.0000000000000721
|View full text |Cite
|
Sign up to set email alerts
|

Using Patient-Reported Outcomes to Measure Symptoms in Children With Advanced Cancer

Abstract: Background Children with advanced cancer experience symptoms despite access to quality care. Symptom research has previously relied upon retrospective designs and parent proxy rather than prospective measurement with self-report. Objective This study evaluated the feasibility of electronic data collection in children with advanced cancer using self-report of symptom frequency, severity, and distress. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…The current analyses address a gap in understanding the similarities and differences of symptom reporting between children with advanced cancer and their parents. The purpose of the primary study was to establish the feasibility of electronic collection of symptom assessments from children with advanced cancer and their parents and describe the symptom experience (Montgomery et al, 2020). The objectives of this subanalysis were to (1) compare reports of symptom prevalence, symptom burden, and symptom frequency, severity, and distress between groups of children and adolescents and their parents, and (2) describe concordance of symptom reports within individual child-parent dyads.…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation
“…The current analyses address a gap in understanding the similarities and differences of symptom reporting between children with advanced cancer and their parents. The purpose of the primary study was to establish the feasibility of electronic collection of symptom assessments from children with advanced cancer and their parents and describe the symptom experience (Montgomery et al, 2020). The objectives of this subanalysis were to (1) compare reports of symptom prevalence, symptom burden, and symptom frequency, severity, and distress between groups of children and adolescents and their parents, and (2) describe concordance of symptom reports within individual child-parent dyads.…”
Section: Purposementioning
confidence: 99%
“…Symptom frequency, severity, and level of distress were assessed further using Likert scales when symptoms were reported as present. Participant responses for symptom frequency, severity, and distress were transformed from categorical to continuous variables on a 0-100 scale and averaged to calculate mean frequency, severity, and distress scores for when a symptom was present (Montgomery et al, 2020). To calculate symptom burden, the mean scores for symptom frequency, severity, and distress were averaged across all reports and reported for each symptom, physical and psychological subscales, and the total scale (Wolfe et al, 2015).…”
Section: Symptom Measurementmentioning
confidence: 99%
“…Pain and nausea are the most prevalent distressing symptoms reported by children with cancer. 5,44 We also found that age had a moderate relationship with pain and nausea and therefore both should be targeted for symptom management especially in older children. Potential strategies that may appeal to adolescents include integrative modalities that have been shown to improve both pain and nausea in children with cancer.…”
Section: Discussionmentioning
confidence: 71%
“…The purpose of this subanalysis was to compare feasibility of electronic data collection data and symptom prevalence, frequency, severity, and distress from children with advanced cancer undergoing HSCT with a non-HSCT cohort. Data were generated from a primary study to evaluate the feasibility of prospective electronic data collection to assess symptoms using patient self-report and to describe the symptom experience in children with advanced cancer (Montgomery et al, 2019).…”
Section: Purposementioning
confidence: 99%
“…The total symptom composite score, consisting of frequency, severity, and distress, was calculated for each symptom endorsed by a patient. Likert-type responses for each symptom domain (frequency, severity, and distress) were log transformed on a scale of 0 to 100, and means for each symptom domain were then calculated (Montgomery et al, 2019;Wolfe et al, 2015). Mean composite scores were also computed for the physical subscale (pain, fatigue, nausea, lack of appetite, shortness of breath, diarrhea, and constipation) and the psychological subscale (sleeping difficulties, irritability, feeling sad, and feeling nervous).…”
Section: Instrument Scoring and Analysesmentioning
confidence: 99%